Analisis Karbon dalam Sedimen pada Ekosistem Lamun di Teluk Gilimanuk, Bali - Vernianda, Cindy; Watiniasih, Ni Luh; Faiqoh, Elok; Giri Putra, I Nyoman (Journal of Marine Research and Technology; Vol 5 No 2 (2022): AUGUST 2022DO - 10.24843/JMRT.2022.v05.i02.p09, 2022)
The increased CO 2 emissions in the atmosphere have caused several environmental changes. Therefore, a larger CO 2 absorption capacity is required. Seagrass can absorb carbon relatively fast and able to store it. Seagrass beds can trap sediment, so the absorption of organic carbon from the sediment by seagrass can be influenced by the size of the substrate. It has been found that the larger the substrate grain, the lower the ability of plants to absorb the organic matter. This study aimed to determine the seagrass density and cover as well as carbon storage in seagrass bed sediments. The variable measured was Sediment-Organic Carbon Content (S-OCC) and Sediment-Organic Carbon Stock (S-OCS) of seagrass ecosystems in Gilimanuk Bay. Employing purposive sampling, 20 sampling points were selected randomly where seagrass beds were present. The data were obtained using a 1×1m quadrant transect. The carbon content of the sediment was calculated by the Loss of Ignition (LOI) method by removing organic matter at a temperature of 600? in a furnace. This study found four seagrass species: Enhalus acoroides, Cymodocea rotundata, Cymodocea serrulate, and Halophila ovalis . The average density of seagrasses in this habitat ranged from 17 – 179 #/m 2 , with seagrass cover values ranging from 25 to 100%. The sediment carbon content, measured as carbon stock, on seagrass ecosystems at Gilimanuk Bay was 0.21% - 5.51% for S-OCC and 0.002 – 0.059 g C org cm -3 for S-OCS. Total S-OCS in Gilimanuk Bay was 11165.84 Mg g C org .